Income inequality and health in Canada, 1981-1996. - Ramage-Morin, Pamela Louise. (University of Ottawa (Canada), 2002)
Background. U.S. and other studies have established an inverse association between a variety of measures of income inequality and population health. Objectives. To describe income inequality (market income and income after tax) and population health (eight measures) in Canada and the provinces between 1981 and 1996; to establish associations between these variables; and to explore whether the associations are measure dependent. Method. Ecologic, analytic, mixed-design study, based on analysis of existing data. Results. The association between the Gini coefficient (market income) and total mortality was very weak in 1981 and 1986, but very strong in 1991 and 1996. Otherwise, associations between income inequality and different health outcomes were non-existent, weak, or sporadic. Conclusions. Income inequality depends on the income concept used. Associations between income inequality and health are measure dependent. Structural changes in Canadian society may account for the emerging association between income inequality and total mortality from 1991 onwards.
Keywords: Canadian Studies.